The Effect of Learning Motivation on English Learning Outcomes at the State of High School 2 Sungai Lilin - Bambang Purwanto, Muhammad (Foreign Language Instruction Probe, 2022)
Based on the results of initial observations, student learning outcomes in English subjects are still not optimal. This can be seen from the acquisition of an average student score of 67, which is still below the predetermined KKM of 70. This problem tends to be influenced by the lack of learning motivation that students have during the learning process, which has an impact on learning English outcomes. This research uses mixed methods. There are 2 types of data analysis tests, simple correlation tests, and descriptive analysis. Based on the results of research and discussion, the conclusions of this study are as follows. 1) The learning motivation of the tenth graders of SMAN 2 Sungai Lilin is good. This is evident from the acquisition of an assessment score of 80.21% in English learning motivation, which is in the good category. Thus, students' motivation in learning English has increased and is categorized as "good," because students' motivation must always be improved so that the learning objectives in each teaching and learning activity are achieved optimally. 2) Student learning outcomes in English lessons in this study are only limited to the cognitive and psychomotor domains, which include knowledge, understanding, application, analysis, and synthesis by emphasizing the aspects of knowledge and understanding that are adjusted to the level of development of the research subject students and motor skills and manipulation of materials or objects. 3) The effect of student learning motivation on student learning outcomes in class X SMAN 2 Sungai Lilin based on the calculation results obtained t-count of 0.821 and t-table of 0.320 at 0.50 and dk = (n-2) = (40-2) = 38. Thus, t-count (0.821) > t-table (0.320), then the hypothesis is accepted. This shows that "student learning motivation affects English learning outcomes.